ICRP Jakarta and Interfaith Marriage Assistance in Indonesia: Civil Rights, Legal Interpretation, and Advocacy for Interfaith Couples - Danu Aris Setiyanto; Sekar Ayu Aryani; Sri Wahyuni (Journal of Islamic Law)
The Indonesian Constitution guarantees its citizens the freedom to express their fundamental rights. However, in practice, this guarantee faces numerous challenges and exceptions, particularly in the context of interfaith marriages. This article aims to explore the role of the Indonesian Conference on Religion and Peace (ICRP) in Jakarta in addressing the phenomenon of interfaith marriages. This study utilises James C. Scott’s theory of resistance to examine how ICRP Jakarta combats stereotypes and negative stigmas associated with interfaith marriages. Data collection techniques include direct field observations and in-depth interviews with twelve key informants, including ICRP Jakarta officials, religious leaders (Islam, Catholicism, and Buddhism), and interfaith couples utilising ICRP Jakarta’s services. A socio-legal approach is employed to demonstrate ICRP Jakarta’s efforts to accommodate interfaith marriage practices. The study finds that ICRP Jakarta’s resistance involves mainstreaming civil rights discourse, interpreting contradictory legal frameworks, and advocating for interfaith couples through juridical, social, and direct advocacy. This article argues that ICRP Jakarta’s resistance to stereotypes and negative stigmas against interfaith marriages exemplifies how research and practical action can foster positive change in a multicultural society. These findings have implications for shaping a more inclusive and tolerant understanding and policy towards interfaith marriages.